Protection of Human Rights Against Criminal Offenders in Detention Process - Maryana, Ana; Farhanudin, Farhanudin; Yusar, Muhamad (Gayaku Publisher, 2022)
The research aims to find out how the Protection of Human Rights for perpetrators of criminal acts in the Detention Process in the Indonesian Criminal Procedure Code. The method used in this study is normative juridical with a statutory approach and a case approach. The data used are secondary data supported by primary legal materials in the form of criminal law books and criminal procedural law books as well as secondary legal materials consisting of legal journals and literature related to the research topic. then collected and analyzed by deductive method. The results of this study state that according to the Criminal Procedure Code those who have the right to detain are investigators, public prosecutors or judges with a certain time limit. In detention must be in accordance with the law. So, detention cannot be carried out arbitrarily. The purpose of detention is for the purposes of investigation, prosecution and examination in court so that the perpetrator does not run away.